Critiquing the Critic: A Reader’s Reaction to Edde Iji’s Black Experience in Theatre (1996) - APEJOYE, Esther Frank (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2023)
Analytical critique is an evaluation of the efficacy and quality of a work, with the longevity of that work possibly being influenced by the outcomes. Furthermore, the term "critique" is often used in contexts of theatre and the arts; readers and reviewers typically focus their critique on objectivity, real-world efficacy, and applicability. Thus, from the above, this work is a critique of Edde Iji’s (1996) Black Experience in the Theatre: The Drama of the Human Condition, which critiques black panoramic achievement in relation to how Africans are portrayed and expressed through some drama and theatre and the understanding of the human condition and experiences. Specifically, Iji (1996) used the comparative studies method to examine the ideological trajectories of some African playwrights and their works, underlying the temperaments that permeate the entire spectrum of drama and theatre across Africa and the diasporas. This work uses the reader’s response theory as well as the analytical critique method to review Edde Iji’s work under consideration. This study re-elucidates Iji’s views on the experiences and conditions of black people on the African continent and in the diaspora, specifically as depicted in the dramatic works of Wole Soyinka, Amiri Baraka, Zulu Sofola, Femi Osofisan, Ola Rotimi, J. P. Clark, and Tunde Fatunde. The work contends that various implausible manifestos have been written in order to undermine the legitimacy of African theatre. However, the black man has often demonstrated beyond a shadow of a doubt the viability of his art. Thus, this work applauds Edde Iji’s insightfulness in expounding, expatiating, and explaining the human predicament specific to the black man.